Using literature circles in the ESL college classroom: a lesson from Puerto Rico - Sambolin Morales, Astrid Nicholl; Carroll, Kevin (Colombian Applied Linguistics Journal, 2015)
This paper will use data collected from a case study of a Basic English course at the University of Puerto Rico where literature circles were used to promote understanding of a novel dealing with issues of race, class and privilege. The article will trace both the implementation of the literature circles and the use of students’ first language to facilitate the reading of The Boy Without a Flag by Abraham Rodríguez Jr. Special attention will be paid to the use of literature circles to promote student participation, both orally and in written form, as well as in discussions of topics relevant to students. The implementation of literature circles in the classroom facilitated student participation, as they worked together to mediate meaning and discuss what they felt was important about the assigned reading. Findings suggest that students benefited from the use of their first language since it served as a cognitive tool that allowed them to collaboratively scaffold while also enabling the instructor to gauge reading comprehension. Moreover, selecting a text whose content tapped into students’ funds of knowledge promoted classroom participation about topics and issues students deemed relevant both inside and outside the English classroom. Key words: literature circles, ESL, adult learners, mother tongue, relevancy Resumen El artículo utilizará datos recopilados a través de una monografía llevada a cabo en un curso de Inglés básico en la Universidad de Puerto Rico, donde se incorporaron círculos literarios para promover la comprensión de una novela que trata sobre los conceptos de raza, clase y privilegio. El artículo trazará la implementación de círculos literarios y el uso del primer idioma de los estudiantes para facilitar la lectura del libro The Boy Without a Flag por Abraham Rodríguez Jr. Se prestará atención especial al uso de círculos literarios para promover participación por parte de los estudiantes, tanto escrita como oral, así como en la discusión de temas relevantes para los estudiantes. Además, dicha implementación de círculos literarios en el salón proveyó oportunidades de diversidad, libre elección e iniciativa para los estudiantes mientras estos trabajaban juntos para mediar significado y discutir lo que a estos le parecía más importante. Los resultados sugieren que los estudiantes fueron beneficiados al utilizar su primer idioma, ya que este sirvió como una herramienta cognoscitiva que les permitió practicar andamiaje colectivo mientras permitió al instructor medir comprensión de lectura. Por último, seleccionar un texto que conecta con los fondos de conocimiento de los estudiantes promovió participación y discusión grupal de temas y asuntos que los estudiantes consideraron relevantes tanto dentro como fuera del salón. Palabras claves: círculos literarios, ESL, estudiantes adultos, primer idioma, relevancia